Towards a history of earthen architecture and construction in Chile, a seismic country - Jorquera Silva, Natalia (Restauro Compás y Canto S.A., 2021)
Chile has a long tradition of building with raw earth, in a big territory of more than 2000 km, which has the particularity of being highly seismic. In recent years, it has been understood that this tradition is part of the country's cultural heritage. However, formal research about earthen heritage is scarce and its history has not yet been written. With that purpose, the research here presented, brought together various sources of information, from which it created a timeline of the use of earth as building material in Chile, divided into five periods: pre-Hispanic, Colonial, Republican, early 20th century and 1990 to nowadays. Each period includes a territory and specific building cultures, typologies and construction techniques, whose linear reading allows us to glimpse the constant search of Chilean builders to find seismic resistant solutions.